2010
DOI: 10.4141/cjps09102
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of phenotypic stability measures for genotypes of three cereal crops

Abstract: Mohammadi, R., Roostaei, M., Ansari, Aghaee, M. and Amri, M. 2010. Relationships of phenotypic stability measures for genotypes of three cereal crops. Can. J. Plant Sci. 90: 819Á830. Multi-environment trial (MET) data are required to obtain stability performance parameters as selection tools for effective genotype evaluation. The main objective of this study was to investigate the interrelationships among nine phenotypic stability methods using grain yield from three sets of cereal experiments [15 durum wheat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
(50 reference statements)
2
31
1
3
Order By: Relevance
“…On the other hand, group 2 has the ω i ;σ ˆ2 di , IPCA1 and GGE biplot statistics, which, in turn, are related to the concept of static stability. However, contrary to the report of Mohammadi et al (2010), some parameters were associated between the 2 groups. It is important to highlight the association of statistics of the ANN method with all other statistics, ranged from r s = 0.48 * to r s = 0.77 ** .…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…On the other hand, group 2 has the ω i ;σ ˆ2 di , IPCA1 and GGE biplot statistics, which, in turn, are related to the concept of static stability. However, contrary to the report of Mohammadi et al (2010), some parameters were associated between the 2 groups. It is important to highlight the association of statistics of the ANN method with all other statistics, ranged from r s = 0.48 * to r s = 0.77 ** .…”
Section: Resultscontrasting
confidence: 54%
“…Tadege et al (2014) reported an association of 0.98 ** between the WR method and E-R regression deviation. Mohammadi et al (2010) reported the association between these 3 methods, with high repeatability between trial groups. This scenario occurred because these parameters indicate stability regardless of the average yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of GEI in national cultivar evaluation and breeding programs has been demonstrated in almost all major crops (Najafian et al, 2010;Zali et al, 2011). Various statistical methods/ models (parametric and non-parametric), concepts, and definitions of stability have been described over the years by many researchers (Lin et al, 1986;Becker and Léon, 1988;Crossa et al, 1990;Lin and Binns, 1994;Hussein et al, 2000;Mohammadi and Amri, 2008;Mohammadi et al, 2010). The model used for GEI is similar to a static or biological concept of stability (Becker and Léon, 1988) and the parameters used in the study are the coefficient of determination (Ri 2 ) (Pinthus, 1973), coefficient of variability (CVi) (Francis and Kannenberg, 1978), and the genotypic variances across environments (Si 2 ) (Roemer, 1917).…”
Section: Introductionmentioning
confidence: 99%